Studying The Relationship Between The Number Of Higher Education Students And Government Spending On It In Syria - أحمد , طالب; درويش , رامي (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to study the relationship between the number of higher education students and government spending on higher education in Syria through the application of ARDL models, and is there a long-term equilibrium relationship between these indicators? The most important results of the study were: There is a short- and long-term relationship between the number of students in public universities and technical institutes on the one hand, and government spending on higher education on the other hand, while there is no short and long-term relationship between the number of higher study and higher institutes on the one hand, and government spending on higher education on the one hand. On the other hand. Based on the error correction model, the indicators of the number of higher education students explain 0.036% of the changes in government spending on higher education in the long run.